Label Propagation for Clustering - Šubelj, Lovro (Advances in Network Clustering and Blockmodeling, 2020)
This chapter presents the basic label propagation method for network clustering and partitioning, together with its numerous variants and advances, extensions to different types of networks and clusterings, and selected large‐scale applications. It discusses the objective function of the label propagation method to shed light on label propagation as an optimization method. As is almost any other clustering method, the label propagation method is nondeterministic and can produce different outcomes on different runs. The chapter discusses different techniques to improve the performance of the label propagation method by either increasing its stability or reducing its complexity. One of the main sources of instability of the method is the random order of label updates in asynchronous propagation. The chapter shows how label propagation can be used effectively for large‐scale community detection, graph partitioning, and identification of structurally equivalent nodes and other network structures.